A taxonomic revision of the Palaearctic genus Roeseliana (Orthoptera: Tettigoniidae: Tettigoniinae: Platycleidini): a case of ongoing Mediterranean speciation - Massa, Bruno; Tagliavia, Marcello; Buzzetti, Filippo Maria; Fontana, Paolo; Carotti, Giovanni; Bardiani, Marco; Leandri, Fausto; Scherini, Roberto; Verde, Gabriella Lo (Zootaxa, 2023)
The genus Roeseliana presently includes 10 specific or subspecific taxa, but following different authors some of them are considered synonyms. However, the authors who have treated these taxa often did not agree with the synonymies, in particular, concerning some taxa, such as R. fedtschenkoi (Saussure, 1874) and R. roeselii (Hagenbach, 1822). The present authors examined hundreds of specimens of different taxa, for the first time were able to obtain the translation from the Russian of the description of R. fedtschenkoi, compared the main morphological characters used to discriminate different taxa, biometrics, bioacoustics and genetics of some taxa. This allowed them to conclude that it is possible to recognize the following taxa: 1) Roeseliana roeselii (Hagenbach, 1822) widespread in the Palaearctic Region and imported in North America; 2) Roeseliana fedtschenkoi (Saussure, 1874) in Uzbekistan and Turkmenistan; 3) Roeseliana pylnovi (Uvarov, 1924) in the Caucasian region; 4) Roeseliana bispina (Bolívar, 1899) in Turkey; 5) Roeseliana azami (Finot, 1892) from the Mediterranean France through Italian peninsula (formerly R. azami minor Nadig, 1961); 6) R. ambitiosa (Uvarov, 1924) on the Balkan peninsula; 7) Roeseliana n. sp. Lemonnier-Darcemont & Darcemont, (in press) on Epirus (Greece and Albania); 8) Roeseliana brunneri Ramme 1951 in north east Italy (Veneto, Friuli and Po Valley); 9) Roeseliana oporina (Bolívar, 1887) in Spain.